Curbing Financial Crimes with Anti-Graft Bureaus in Nigeria: The Accountants' Perception - Ahmad Bukola Uthman; Lukman Adebayo Oke; Mohammed Kayode Ajape; Zayyad Abdul-Baki; Murhtala Oladipupo Tijani (Journal of Accounting and Management Information Systems (JAMIS), 2015)
Corruption, be it financial or non-financial is a global cankerworm that has eaten deep into the fabrics of many nations and war against it has been a recurring decimal in every economy. In Nigeria, recent attempts at nipping corruption in the bud gave rise to some anti-graft agencies such as the Economic and Financial Crimes Commission (EFCC). Against this background, opinion of 140 accountants in various capacities was sought on the efficacy of the anti-graft agencies in curbing financial crimes through a survey questionnaire. The study found that respondents group perceived the anti-graft agencies as highly effective but could not establish that accountants in various walks of life differ significantly in their perception of the efficacy of the Nigerian Anti-graft bureaus (Overall Mean= 2.98, F= 2.263 and P>0.05) using ANOVA as statistical analysis tool. It was recommended that Nigerian government should strengthen the Anti-financial crimes agencies given that the influence of highly placed offenders, the dignity, societal bondage and shame inherent in financial crimes may affect the potency of anti-financial crimes measures put in place.
Keywords: D04; H24; M48; 650; Financial crimes; anti-graft bureaus; opportunity theory; defiance theory; Nigeria